PERSEPSI PENGGUNA LAYANAN KESEHATAN PRIMER MENGENAI KUALITAS PELAYANAN PADA PUSKESMAS BADAN LAYANAN UMUM DI KABUPATEN GIANYAR - Listyowati, Rina; Indrayathi, Putu Ayu; Sri Nopiyani, Ni Made (ARCHIVE OF COMMUNITY HEALTH; Vol 3 No 1 (2016): Juni (2016), 2016)
One of the reasons for establishing Public Service Agency (BLU) policy at Community Health Care Centers is the number of complaints for poor quality services. This policy was implemented in January 2010 by the Gianyar Government in every Community Health Care Center in Gianyar.  This is the realization of the Gianyar Government's attention in improving the quality of the Community Health Care Center Services.  This study aims to determine the public perception of the quality of services provided by the Community Health Care Center in Gianyar District. This study was a cross-sectional analytic study and conducted at four Community Health Care Centers with BLUD’s status in Gianyar District with 105 respondents selected by multistage random sampling method. The data collection included survey questionnaires and analyzed descriptively by chi square test. The results showed that overall the respondents had a "good" perception towards the elements of Community Health Care Center services with BLU status in Gianyar District. However, there are three elements that were "perceived as poor" comprising responsiveness (14.3%), accuracy (11.4%) and environmental comfort (12.4%). The results of the chi square test showed that there were significant differences between the age factors with the respondent perceptions of service quality in Community Health Care Center with BLU status (p = 0.004), but gender, education level and occupation did not have a meaningful relationship. This research suggests that the Health Office should increase the intensity of coaching and facilitation of procedures related to the Community Health Care Center so that the expected performance of attendant care becomes more patterned.
Keywords: quality of care, community health care center, local public service agencies (BLUD)